Can land-use and land-cover change explain reduced resilience in forests? - Alibakhshi, Sara; Azadi, Hossein; Espinosa-Leal, Leonardo (Frontiers in Earth Science, 2024)
Generating signals of reduced resilience in ecosystems is crucial for conservation and management endeavors. However, the practical implications of such systems are still limited by the lack of data and uncertainties associated with predicting complex systems such as ecosystems. This study aims to investigate the potential of time series analysis of remote sensing data in detecting signals of reduced resilience in mangrove forest ecosystems. Using time series analysis of remote sensing images, the resilience of mangrove forests was explored across two distinct study sites. One site (Qeshm Island) has been adversely affected by land-use and land-cover changes, while the other (Gabrik) serves as a reference ecosystem. The study uses data from the Moderate Resolution Imaging Spectroradiometer (MODIS) satellite to quantify three remotely sensed indices: the Normalized Difference Vegetation Index (NDVI), the Modified Normalized Difference Water Index (MNDWI), and the Modified Vegetation Water Ratio (MVWR). In addition, Landsat data has been used to explore temporal alterations in land-use and land cover. Trend analyses focused on autocorrelation (acf(1)) and standard deviation (SD) metrics to identify resilience reduction signals. For Qeshm Island, significant upward trends in NDVI metrics indicated decreased resilience (Kendall’s τ of acf(1): 0.50, SD: 0.90), a contrast to stable metrics in Gabrik (Kendall’s τ of acf(1): -0.19, SD: -0.19). MNDWI showed reduced resilience in both sites but was more pronounced in Qeshm Island (Kendall’s τ of acf(1): 0.86, SD: 0.90) than in Gabrik (Kendall’s τ of acf(1): 0.79, SD: 0.90). MVWR, however, did not effectively signal reduced resilience in either location. These findings may be explained through quantitative analyses of land-use land-cover change. Qeshm Island underwent drastic increases in the built-up class by a 64.40% change between 1996 and 2014, whereas the built-up class expanded modestly by a 4.04% change in the Gabrik site. The findings of this study can be integrated with ecosystem management tools to enhance the effectiveness of conservation efforts. This is the first report of the successful application of remote sensing in generating signals of reduced resilience within mangrove forests in the Middle East.